William Least Heat-Moon’s American Travels: Representing Spaces through the American Road Narrative ([Inter]sections, 2025)
William Least Heat-Moon embarked on a road trip across the United States in 1978, after having lost his job as a professor and after divorcing. With his van, called Ghost Dancing, after Native American ceremonies, Heat-Moon hits the open road for three months, travelling only through the backroads of America, with the intention to find pristine places. These experiences on the road are recounted in his well-known road book Blue Highways: A Journey into America (1982). The aim of this article is to discuss the representation of space—natural and manmade—within Heat-Moon’s Blue Highways, using ecocritical and geocritical studies as a methodological mapping for the analysis. Applying the ecocritical and geocritical approaches will contribute to provide a more comprehensive study on the topic of space, leading also to a reconsideration of the genre of the American road narrative, and consequently, providing new insights on mobilities and space studies.